Profit Management Policy: Profitability And Leverage In Manufacturing Companies - Irfan, Irfan (CERED Indonesia Institute, 2025)
This study aims to determine the effect of profitability and leverage on earnings management in Food and Beverage Manufacturing Companies listed on the IDX for the 2019-2023 period. The population of this study was 40 companies and a sample of 15 companies within a period of 5 years. The sampling technique used was purposive sampling technique. The data used were secondary data, namely quantitative data. The analysis method used was descriptive analysis and multiple linear regression analysis, then tested in the classical assumption test. In this study, earnings management was measured using discretionary accruals (modified Jones), profitability was measured using return on assets (ROA), leverage was measured using the debt to asset ratio (DAR). The results of this study indicate that profitability and leverage do not have a simultaneous and insignificant effect on earnings management. and the partial test results in two independent variables show that profitability has a negative and insignificant effect on earnings management and leverage has a positive and significant effect on earnings management